R&D, Marketing Innovation, and New Product Performance: A Mixed Methods Study1. Issue 3 (19th January 2017) - Grimpe, Christoph; Sofka, Wolfgang; Bhargava, Mukesh; Chatterjee, Rabikar
Abstract : This paper investigates the relationship between investments in marketing innovation, that is, the way in which technologically unchanged products are designed, priced, distributed, and/or promoted, and a firm's new product performance. Marketing innovation, such as calorie‐based packaging or unusual distribution channels, may lead to new products. However, it is unclear whether they pay off, particularly when the firm follows a dual strategy, that is, investing in both innovative marketing and R&D at the same time. We draw from theory on competence development as well as diffusion of innovation and argue that pursuing a dual strategy lowers performance, an effect that we attribute to the role of complexity in innovation. Based on a mixed methods study that integrates a data set of 866 firms from a representative set of industries in Germany and extensive interview evidence, we find empirical support for our hypotheses. Our research contributes to the emerging stream of literature that seeks to better understand the role of marketing in firms' innovation processes.